THE EFFECT OF RISK BASED CAPITAL ON THE PROFITABILITY OF INSURANCE COMPANIES REGISTERED WITH THE FINANCIAL SERVICES AUTHORITY - Aulia, Syahputri (JMRI Journal of Multidisciplinary Research and Innovation, 2024)
This research aims to determine the development of Risk Based Capital, profitability, and the effect of Solvency Rate Limit (RBC) on profitability in Syariah Unit Insurance registered with the Financial Services Authority. This research is a quantitative research, and the source of data obtained is secondary data. The population is 25 Syariah Unit General Insurance companies registered with Financial Services Authority (OJK). This research sample uses a purposive sampling technique by 9 Syariah Unit General Insurance companies registered with OJK using annual financial statements in accordance with the variables used during the period (2018-2023). The data analysis uses multiple linear regression analysis with a constant of 41.513 which means, if the Risk Based Capital variable is fixed, then the Return On Asset will increase by 41.513 and the regression coefficient value for the Investment variable in the regression equation shows a positive value of 0.023 X, this means that if the Risk Based Capital variable is fixed, then the Return On Asset variable will increase by 0.023. The Coefficient of Determination (R) for Risk Based Capital on Return On Asset is 0.609, then for the Risk Based Capital variable on Return On is 0.515. And the Analysis of the Hypothesis Test is known that Risk Based Capital (X) shows at an alpha coefficient of 5% (t-stat = 3.119 > 1.674) and prob. 0.006 < 0.05. So the hypothesis is accepted, namely Risk Based Capital has a significant effect on Return On Equity in the Alpha 5% Syariah unit insurance company.